การเตรียมผงแบคทีเรียเซลลูโลสสำหรับวัสดุทางการแพทย์: ส่วนที่ 1 - ศิริดำรง พรเพ็ญ; วัยโรจนวงศ์ ธนิสร์; พูนธนานิวัตกุล ฉวีวรรณ; เรืองโสภาพันธ์ กฤต; สีจันทร์ ราชพร; บุญเรือง อาจินต์; ลุมพิกานนท์ ณรงค์ (Science Essence Journal, 2018)
บทคัดย่อ งานวิจัยนี้ศึกษาผลของการเตรียมผงแบคทีเรียเซลลูโลส ต่อสมบัติทางกายภาพ ทางเคมีและทางชีวภาพ โดยหมักด้วยน้ำตาลกลูโคสจากข้าวไทย สารสกัดจากยีสต์ น้ำกลั่นและ Acetobacter xylinum TISTR 975 เป็นเวลา 7 วัน จากนั้นจึงเตรียมเป็นผงแบคทีเรียเซลลูโลส ด้วยวิธีที่แตกต่างกัน ได้แก่ การใช้น้ำ สารละลายโซเดียมไฮดรอกไซด์ และบดเปียก และแช่เย็นที่อุณหภูมิ -20 องศาเซลเซียส แล้วทำให้แห้ง ที่อุณหภูมิ -60 องศาเซลเซียส นาน 3 วัน จากนั้นจึงบดด้วยเครื่องบดความเร็ว 20,000 รอบต่อนาที จนได้ผงละเอียด นำไปวัดลักษณะของผงแบคทีเรียเซลลูโลสด้วยกล้องจุลทรรศน์อิเล็กตรอนแบบส่องกราด วัดการกระจายตัวของอนุภาค และการวิเคราะห์การเลี้ยวเบนรังสีเอ็กซ์ พบว่าผงที่ได้จากทั้งสามวิธีมีโครงสร้างระดับนาโนเมตร/ไมโครเมตร ผลจากการวิเคราะห์การเลี้ยวเบนรังสีเอ็กซ์ แสดงลักษณะช่วงพีคที่ 2q ที่ 15oและ 22o ซึ่งผงแบคทีเรียเซลลูโลสที่เตรียมทั้ง 3 วิธี มีขนาดอนุภาค32และ 1449 ไมโครเมตร ตามลำดับ จากผลการตรวจสอบความเป็นพิษด้วยวิธี MTT ของผงแบคทีเรียเซลลูโลสที่เตรียมได้พบว่าเซลล์มีชีวิตรอด 97% ผลการวิจัยที่ได้แสดงว่าผงแบคทีเรียเซลลูโลสที่เตรียมโดยการใช้น้ำและการบดเปียกสามารถใช้เป็นวัสดุทางการแพทย์สำหรับใช้ในงานวิจัยต่อไป - - - Preparation of Bacterial Cellulose Powder for Medical Materials: Part I ABSTRACT In this research, effects of preparation techniques of bacterial cellulose (BC) powder on physical, chemical and biological properties were investigated. The BC sheets were prepared by fermentation with glucose of Thai rice, yeast extract, distilled water and Acetobacter xylinum TISTR 975 for 7 days. The BC sheets were further treated by three different techniques including water, NaOH and wet grinding treatment. The BC was neutralized, squeezed out water and kept in –20 oC. The BC frozen-sheets were lyophilized at -60 oC about 3 days. The BC dry-sheets were finally pulverized at 20,000 rpm until fine powder was obtained. The characterizations of BC powders were measured by Scanning Electron Microscopy (SEM), particle size distribution, and X-ray Diffraction analysis (XRD). SEM micrographs of BC powder obtained from all three treatment methods revealed nano- /micro- fibrils structures. XRD pattern showed two principle diffraction peaks of 2Ɵ at 15v and 22.5o where particle size of water treated BC and wet grinding treated BC powder were about 190 and 716 µm, respectively. The MTT cytotoxicity of the obtained BC powder was studied using Human Gingival Fibroblast (HGF) at passage 6. The results showed 97% cell viability which is the same to that of commercial product. The results were supported that BC powders prepared from water treated and wet grinding methods can be used as medical materials for the next research.